Relationship of blood pressure, antihypertensive therapy, and outcome in ischemic stroke treated with intravenous thrombolysis: retrospective analysis from Safe Implementation of Thrombolysis in Stroke-International Stroke Thrombolysis Register (SITS-ISTR) - Ahmed, Niaz; Wahlgren, Nils; Brainin, Michael; Castillo, José; Ford, Gary A.; Kaste, Markku; Lees, Kennedy R.; Toni, Danilo; Hacke, Werner; Hennerici, Michael G. (Stroke, 2009)
BACKGROUND AND PURPOSE: The optimal management of blood pressure (BP) in acute stroke remains unclear. For ischemic stroke treated with intravenous thrombolysis, current guidelines suggest pharmacological intervention if systolic BP exceeds 180 mm Hg. We determined retrospectively the association of BP and antihypertensive therapy with clinical outcomes after stroke thrombolysis. - METHODS: The SITS thrombolysis register prospectively recorded 11 080 treatments from 2002 to 2006. BP values were recorded at baseline, 2 hours, and 24 hours after thrombolysis. Outcomes were symptomatic (National Institutes of Health Stroke Scale score deterioration >or=4) intracerebral hemorrhage Type 2, mortality, and independence at (modified Rankin Score 0 to 2) 3 months. Patients were categorized by history of hypertension and antihypertensive therapy within 7 days after thrombolysis: Group 1, hypertensive treated with antihypertensives (n=5612); Group 2, hypertensive withholding antihypertensives (n=1573); Group 3, without history of hypertension treated with antihypertensives (n=995); and Group 4, without history of hypertension not treated with antihypertensives (n=2632). For 268 (2.4%) patients, these data were missing. Average systolic BP 2 to 24 hours after thrombolysis was categorized by 10-mm Hg intervals with 100 to 140 used as a reference. - RESULTS: In multivariable analysis, high systolic BP 2 to 24 hours after thrombolysis as a continuous variable was associated with worse outcome (P<0.001) and as a categorical variable had a linear association with symptomatic hemorrhage and a U-shaped association with mortality and independence with systolic BP 141 to 150 mm Hg associated with most favorable outcomes. OR (95% CI) from multivariable analysis showed no difference in symptomatic hemorrhage (1.09 [0.83 to 1.51]; P=0.58) and independence (1.03 [0.93 to 1.10]; P=0.80) but lower mortality (0.82 [0.73 to 0.92]; P=0.0007) for Group 1 compared with Group 4. Group 2 had a higher symptomatic hemorrhage (1.86 [1.34 to 2.68]; P=0.0004) and mortality (1.62 [1.41 to 1.85]; P<0.0001) and lower independence (0.89 [0.80 to 0.99]; P=0.04) compared with Group 4. Group 3 had similar results as Group 1. - CONCLUSIONS: There is a strong association of high systolic BP after thrombolysis with poor outcome. Withholding antihypertensive therapy up to 7 days in patients with a history of hypertension was associated with worse outcome, whereas initiation of antihypertensive therapy in newly recognized moderate hypertension was associated with a favorable outcome.
SITS Investigators: Nils Wahlgren, Antoni Davalos, Gary A. Ford, Martin Grond, Werner Hacke, Michael Hennerici, Markku Kaste, Vincent Larrue, Kennedy R. Lees, Risto Roine, Danilo Toni
Gesehen am 20.04.2022